The Viking Age and the Crusades Era in Yngvars saga víðförla - Glazyrina, Galina (Universität Tübingen, 2004)
The history of Sweden was not a priority subject for saga writers in Iceland. The "Saga of Ingvar the Far-Traveller" (YS) is based on a reliable fact, justified by about 25 runic inscriptions which date to the first half of the eleventh century, that a military expedition, led by Ingvar, went from Sweden to Eastern Europe, then moved to the South or to the South-West and perished there. The plot was revived by an Icelandic cleric who compiled the YS. His special interest towards the episode of the history of Sweden might have been provoked by the fact that at his time (beginning in the end of the twelfth century and through the thirteenth century) Sweden was active in pursuing its own missionary activity in the East Baltic region. The author of the YS constructed his saga on the principles typical of Icelandic fornaldarsögur, relating a story of a journey to a marvelous world. The plot itself provided the author of the saga with vast opportunities for the development and together with other features it was supplied with episodes and descriptions similar to those which are found in abundance in Latin Chronicles of the Crusades and other sources. The basic opposition of the chronicles between the Christians and the Muslims is presented in the YS as the opposition between the Christian Scandinavians and the pagans. Thus the historical fact of a real expedition of the Swedes to the East got a new interpretation: the story of Ingvar became a "missionary" (as Hermann Pálsson and Paul Edwards called it) saga.